Diagnosis and Treatment of Keloid: Method Summary and Effect Evaluation - Liu Y; Xiong X; Cao N; Zhao Y (Dove Medical Press, 2023)
Yu Liu, Xiaoliang Xiong, Nan Cao, Yinlong Zhao Nuclear Medicine Department, Jilin University Second Hospital, Changchun, Jilin Province, People's Republic of ChinaCorrespondence: Yinlong Zhao, Email yinlong@jlu.edu.cnAbstract: Keloid is a prevalent skin disorder characterized by the abnormal growth of keloid tissue, which usually occurs following wound healing or surgical incisions. It typically progresses through several stages: the inflammatory stage, the proliferative stage, collagen remodeling, and ultimately the formation of keloid. This review aims to summarize the diagnostic and therapeutic methods for keloid, and evaluate their effectiveness. The diagnosis of keloid is usually based on medical history and clinical manifestations such as pain, itching, erythema, and induration. Other commonly used diagnostic methods include tissue biopsy and ultrasound examination. Various treatment options for keloid exist, including physical therapy, medication, surgical treatment, and radiation therapy. Physical therapy includes pressure therapy, laser therapy, such as silicone sheets, elastic bandages, and laser irradiation. Medication treatment mainly involves the application of topical medications or intralesional injections, such as topical corticosteroids, 5-fluorouracil, and others. Radiation therapy can be administered using applicators and superficial radiation therapy, among other methods. The treatment outcomes of keloid vary from person to person and recurrence is common. Therefore, a comprehensive treatment approach may be the most effective strategy. Individualized treatment plans should consider factors such as the patient's age, gender, medical history, and the severity of the condition. In conclusion, the diagnosis and treatment of keloid require consideration of multiple factors and the implementation of individualized treatment plans. Future research should focus on identifying the molecular mechanisms underlying the occurrence and progression of keloid in order to develop more effective treatment methods.Keywords: keloid, pathogenesis, clinical treatment